1998
DOI: 10.1007/s001980050069
|View full text |Cite
|
Sign up to set email alerts
|

Bone Changes in Pre- and Postmenopausal Women with Thyroid Cancer on Levothyroxine Therapy: Evolution of Axial and Appendicular Bone Mass

Abstract: The effects of suppressive doses of levothyroxine (LT4) on bone mass are controversial. Our aim was to evaluate the effects on axial and appendicular bone mineral density (BMD) and bone metabolism of long-term LT4 suppressive therapy in women by means of cross-sectional and longitudinal studies, and also to assess the potential influence of menopausal status and LT4 dose. Seventy-six women (aged 47 +/- 13 years, 37 pre- and 39 postmenopausal) on suppressive therapy (67 +/- 34 months duration, mean LT4 dose 168… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 33 publications
1
45
0
1
Order By: Relevance
“…Previous studies in patients with well-differentiated thyroid cancer receiving suppressive LT 4 therapy have shown conflicting results: no decrease in BMD at any age [5,6], bone loss only in postmenopausal women [17], or deleterious effects in both premenopausa and postmenopausal patients [18,19]. Systematic reviews of BMD in these patients have reported diverse conclusions [3,4].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in patients with well-differentiated thyroid cancer receiving suppressive LT 4 therapy have shown conflicting results: no decrease in BMD at any age [5,6], bone loss only in postmenopausal women [17], or deleterious effects in both premenopausa and postmenopausal patients [18,19]. Systematic reviews of BMD in these patients have reported diverse conclusions [3,4].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, two reported metaanalyses have suggested that suppressive doses of T 4 in postmenopausal women lead to increased bone loss of w1% per annum (Faber & Galloe 1994, Uzzan et al 1996. Eight studies have also included male patients, but only one reported a reduction of BMD in men receiving suppressive doses of T 4 (Jodar et al 1998). Consistent with this, a metaanalysis concluded that suppressive doses of T 4 had no effect on BMD in men (Uzzan et al 1996).…”
Section: Suppressive Doses Of T 4 In Differentiated Thyroid Cancermentioning
confidence: 97%
“…The increase in OPG with age and markers of bone turnover further confirms the protective role of the cytokine against bone loss [42]. The cause of bone loss after long-term sustained hyperthyroxinemia [21,25,[28][29][30]53] will be more extensively studied in the light of new knowledge on the OPG and RANK/RANK-L systems. Finally, the controversial extrathyroid action of TSH on bone [54] must be considered in this new scenario.…”
Section: Discussionmentioning
confidence: 77%
“…The effect of subclinical hyperthyroidism on bone mineral density (BMD) is controversial [25][26][27], but could be significant in patients with differentiated thyroid carcinoma (DTC) who receive suppressive long-term doses of levothyroxine (L-T4) after total thyroidectomy [28,29]. Some authors [30] have shown that L-T4 suppressive therapy for at least 1 year in premenopausal women with DTC causes a reduction in BMD of the femoral neck, femoral trochanter, and Ward's triangle, whereas others [31,32] were unable to exclude the possibility that long-term suppressive doses of L-T4 do not decrease BMD.…”
Section: Introductionmentioning
confidence: 99%